All We Need Is Trust: How the COVID-19 Outbreak Reconfigured Trust in Italian Public Institutions - Falcone, Rino; Colì, Elisa; Felletti, Silvia; Sapienza, Alessandro; Castelfranchi, Cristiano; Paglieri, Fabio (Frontiers in Psychology, 2020)
The central focus of this research is the fast and crucial impact of the COVID-19 pandemic, and its exceptionally serious consequences in terms of healthcare, state intervention and impositions, radical changes in people’s life, on a crucial psychological, relational, and political construct: trust. In this survey, addressed to 4260 Italian citizens, we tried to analyze and measure such impact, focusing on various aspects of trust. This attention to multiple dimensions of trust constitutes the key conceptual advantage of this research, since trust is a complex and layered construct, with its own internal dynamics. In particular, the analysis focuses on how citizens attribute trust to Public Authorities, in relation to the management of the health crisis: with regard to the measures and guidelines adopted, the purposes pursued, the motivations that determine them, their capacity for involvement and their effectiveness for the containment of the virus itself. A pandemic creates a bilateral need for trust, both in Public Authorities (they have to rely on citizens’ compliance, and must try to promote and maintain their trust in order to be effective), and in citizens, since they need to feel that somebody can do something, can (has the power) to protect them, to act at the needed collective level. We are interested to explore how this need for trust affects the attributional process, regarding both attitudes and the corresponding decisions and actions. The most striking result of this survey is the very high level of institutional trust expressed by respondents: 75% of them trust Italian public authorities to be able to deal with the COVID-19 emergency. This is in sharp contrast with the relatively low levels of institutional trust characteristic of Italy, both historically and in recent surveys. Moreover, the survey allowed to discriminate several potential predictors for trust, thus emphasizing factors that, during this crisis, are exhibiting an anomalous impact on trust.